The Meaning of Syiqaq In The Qur'an : Analysis Semantics of The Perspective Toshihiko Izutsu - Muhammad Fatkhur Rosyid; Kharis Nugroho; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2024)
Understanding the meaning of the Quran correctly and in accordance with the intention of the revelator is very important so that the Quran can be understood by mankind. In this context, a correct understanding of the word “syiqaq” in the Quran is crucial, so an in-depth study of all words related to Shiqaq is needed to obtain a complete meaning. There are various approaches that can be applied in understanding the Qur'an, one of which is the semantic approach developed by Thoshihiko Izutsu. This research method uses library research, as well as component analysis formulated by Izutsu. The purpose of this study is to examine the concept of the word Syiqaq in the Quran from a semantic perspective. In this study, the word Syiqaq is analyzed based on semantic theory, both in terms of context and meaning contained, as well as mentioning the derivation of the word in the Quran. The use of the word Syiqaq in the Quran, which appears in various forms and grammatical structures, produces a variety of meanings, thus creating variations in its interpretation. Some of the meanings of Syiqaq and its derivatives in the Quran include misguidance, difference and enmity.